2014
DOI: 10.1038/ncomms6188
|View full text |Cite|
|
Sign up to set email alerts
|

Camelid genomes reveal evolution and adaptation to desert environments

Abstract: Bactrian camel (Camelus bactrianus), dromedary (Camelus dromedarius) and alpaca (Vicugna pacos) are economically important livestock. Although the Bactrian camel and dromedary are large, typically arid-desert-adapted mammals, alpacas are adapted to plateaus. Here we present high-quality genome sequences of these three species. Our analysis reveals the demographic history of these species since the Tortonian Stage of the Miocene and uncovers a striking correlation between large fluctuations in population size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
324
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(358 citation statements)
references
References 63 publications
30
324
4
Order By: Relevance
“…This appears to be common among species that are adapted to desert and desert-like environments. For instance, in a comparative genomic analysis, Wu et al (2014) revealed complex features, such as fat and water metabolism, stress response to heat and aridity, intense ultraviolet radiation and chocking dust, in the genome architecture of camelids that are related to adaptation to desert environments.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be common among species that are adapted to desert and desert-like environments. For instance, in a comparative genomic analysis, Wu et al (2014) revealed complex features, such as fat and water metabolism, stress response to heat and aridity, intense ultraviolet radiation and chocking dust, in the genome architecture of camelids that are related to adaptation to desert environments.…”
Section: Discussionmentioning
confidence: 99%
“…These animals have served for traditional technologies since the very early era of domestication (Elsik et al 2009;Archibald et al 2010;Dong et al 2013;Wu et al 2014). In addition, some of domestic even-toed ungulates are now used as animal models in biomedical researches to investigate the genetic basis of complex traits, to produce transgenic peptide medicines, and to come up with some special form of antibody offering particular advantages in various medical and biotechnological applications (Kastelic et al 2009;Jirimutu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This multipurpose animal has outperformed all other domestic mammals, including the donkey, in arid environments and continues to provide basic commodities to millions of people inhabiting marginal agro-ecological zones. In the current context of advancing desertification and global climate change, there is renewed interest in the biology and production traits of the species (2), with the first annotated genome drafts having been recently released (3,4).…”
mentioning
confidence: 99%